Sztuka wojenna słowian w świetle dzieła Teofilakta Symokatty. - Różycki, Łukasz (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2016)
The purpose of the piece Sztuka wojenna Słowian w świetle dzieła Teofilakta Symokatty [The military craft of Slavs as presented in the work of Theophylat Simocatta] was to demonstrate the military history of Slavs in the context of the work of Theophylact Simocatta, a leading source of information about the Balkans at the end of the 6th century. All the fragments including any information about Slavs’ military operations were analyzed and then verified against other contemporary sources, mainly the military treatise Strategikon. The results were anything but dubious; Theophylact’s account of Slavs was corroborated not only in the works of other historians (Procopius and John of Ephesus), but also in a military treatise, most likely written by an experienced commander (Strategikon). The work of Theophylact presents Slavic war craft as a simple, tribal affair. The barbarians made use of all the available stratagems in order to gain advantage over Romans whose military experience and material culture surpassed that of Slavs. Accounts of ambushes, night raids, swift attacks and rapid retreats (especially mentions of how the Slavs adapted to fighting in the woods) appear in all reliable sources. Another frequently mentioned fact is Slavs’ skill in crossing rivers in which they excelled. A comparative analysis of the sources confirms that all ancient authors regarded Slavs highly skilled in this respect. Another conclusion was that Slavs acted differently in Roman territories (where in the event of an attack, they would typically retreat) than in their own lands which they were prepared to defend at any cost. A verification of the reliability of Theophylact Simocatta’s account of the Slavic military craft gives grounds for attempting a more detailed assessment of their activities in the final two decades of the 6th century, and as such adds to our knowledge about barbarian tribes penetrating the Balkans.